Optimization by response surface methodology for production of β-galactosidase from Enterococcus faecium using recycled medium (Research, Society and Development, 2020)
In this study, recycled medium from three photosynthetic microorganisms (Chlorella vulgaris, Dunaliella tertiolecta and Arthrospira platensis) was evaluated for use in producing β-galactosidase, an enzyme traditionally used to degrade lactose in dairy products. Recycled medium from Chlorella vulgaris was selected to optimize culture medium to be used to produce β-galactosidase by Enterococcus faecium in submerged fermentation. Response Surface Methodology (RSM) was used to optimize the levels of the variables: temperature (30-40°C), lactose concentration (0-5%), fermentation time (12-24h), pH (6-8) and their interaction. All variables studied had a statistically significant effect on the production of β-galactosidase. The optimal conditions for producing the enzyme were achieved: temperature of 31ºC, lactose concentration of 5.34%, fermentation time of 12h and pH of 8.0. Under these conditions, the β-galactosidase activity was 29.85 U/mL which was quite close to the predicted value (30.83 U/mL). Finally, it can be concluded that recycled medium from optimized C. vulgaris supernatant may well be important for the biotechnology industry as it is an abundant low-cost source for producing β-galactosidase by Enterococcus faecium.